Sociodemographic factors associated with dental students knowledge and attitudes regarding disinfection as a control measure to reduce the spread of COVID-19 - Geanella Silva-Robles; Gissela Briceño-Vergel; Rosa Aroste-Andía; Emily Hernández-Huamaní; Marysela Ladera-Castañeda; Miriam Castro-Rojas; Percy Gavilán-Chávez; Luis Cervantes-Ganoza; César Cayo-Rojas (Scientific Reports)
Abstract Despite maintaining a lower mortality rate and greater control of victims infected by COVID-19, the world’s population and science are still confronted with this coronavirus. Therefore, the aim was to assess the association between sociodemographic factors and the level of knowledge and attitudes of dental students regarding disinfection as a control measure to reduce the spread of COVID-19. This cross-sectional study evaluated 503 dental students from the capital city and one Peruvian province between February and June 2022. A validated 13-item questionnaire was used. A Poisson regression model with robust variance was used to evaluate the influence of the variables sex, age, year of study, marital status, place of origin, death of a family member due to COVID-19, and history of COVID-19, with the level of knowledge and attitudes of the dental students, considering a significance level of p < 0.05. Of the total participants, 14.3% showed sufficient knowledge, and 89.3% showed positive attitudes regarding disinfection as a control measure to reduce the spread of COVID-19. Furthermore, those from the capital city were 52% less likely to have sufficient knowledge regarding disinfection as a control measure to reduce the spread of COVID-19, compared to those from the province (APR = 0.48; 95% CI: 0.31–0.75). Moreover, none of the variables considered in this study were significantly associated with attitudes toward this topic (p > 0.05). A minority of dental students presented sufficient knowledge, while the majority presented positive attitudes regarding disinfection as a control measure to reduce the spread of COVID-19. In addition, being from the capital city was a limiting factor for sufficient knowledge. The variables sex, age, year of study, marital status, place of origin, death of a family member due to COVID-19, and history of COVID-19 were not influential factors for positive attitudes on this topic.